Distribution of nucleosome binding motifs around the functional sites of human housekeeping genes - Bao, Tonglaga; Li, Hong; Zhao, Xiaoqing (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
The positioning of nucleosome on underlying DNA plays an important role in the regulation of every process that occurs on DNA. We plotted out the nucleosome binding motifs around the functional sites of housekeeping genes and compared the similarities and differences with ensemble genes. We found that housekeeping genes show stronger preference than ensemble genes. Proportion of nucleosome binding motifs in the transcription start region is higher than other functional sites. Our result confirmed the idea that nucleosomes are distributed not uniformly along the genomic DNA and more nucleosome binding signal existed in the transcription start region to facilitated gene transcription and expression.